Métaphore de l’Amour dans les Paroles de l’Album «D’eux» de Céline Dion - Laksman-Huntley, Myrna; Fardanira, Raissa Annisa (Lingua Litteria Journal, 2021)
This research discusses the metaphorical elements contained in the song lyrics of Celine Dion's album D'Eux. From this study, it was found that there are 26 verses from 3 songs, titled "Pour que tu m'aimes encore", "J'irai oÃ¹ tu iras", and "Je sais pas", which contain metaphors. The analysis in this study uses the component theory of meaning from Mortureux (1997) and the theory of metaphors from Camp (2003). The results showed that the songs in this album all have the thematic characteristics of love, but with different depictions of it. The producerâ€™s aim in making this album was to dedicate and show the singerâ€™s love and gratitude for her life. The dominant metaphor function used in lyrics is to provide a clear picture of the true meaning. The love metaphor in the song â€œPour que tu m'aimes encoreâ€ tells of the loss of a partner, â€œJ'irai oÃ¹ tu irasâ€ about the husband she admires, and â€œJe sais pasâ€ describes her dependence on her husband. We have found that the lyrics in the three songs are proven to have metaphorical elements of love and form the identity of each song. Each song has a different meaning of love, but has one thing that is highlighted in common, namely the effort to fight for love.